Perancangan Sistem Informasi Penilaian Siswa Berbasis Web Pada SMK Negeri 1 Muara - Rivon Fotriyodi (PT. ALHAFI BERKAH INDONESIA, 2023)
The use of a semi-manual system in SMK Negeri 1 Muara until now there are still shortcomings that are still experienced by the agency certainly affects whether or not the information generated. The occurrence of data inaccuracies is an obstacle that is still experienced by agencies, such incidents are certainly very influential on the information generated. The data that has been collected is then analyzed to find out the problem and the system that is running within the agency. The method used in conducting research is descriptive method, while the data collection methods are preliminary surveys and field surveys, namely interviews, observation, and literature study. The system analysis technique used by the writer is the Unified Modeling Language (UML) modeling technique. The analysis technique and system design used in this study is object-oriented technique. Based on these results, the authors build information systems applications using the PHP programming language and HTML, MySQL as a database to support the availability of better information, and offer a faster presentation of reports to assist agencies in making decisions. The information system is expected to produce accurate information for the right decision making so that it can provide good service to students. Suggestions are given so that the system can run well namely the use of the system must be wise according to the existing procedures and training needed for system users. Agencies are advised to do a database backup on the system to prevent database damage that can result in loss of data that has been stored.